2007
DOI: 10.1007/s10549-007-9814-2
|View full text |Cite
|
Sign up to set email alerts
|

Population attributable risks for breast cancer in Swedish women by morphological type

Abstract: The purpose of this population-based cohort study is to describe the etiology of invasive and in situ breast cancer, using the Swedish Family-Cancer Database. A total of 1,028,455 women, aged 40-61 years, were followed from 1993 through 2004. Invasive and in situ breast cancer was identified in 27,243 and 3,496 women, respectively, with data on family history, reproductive variables, residential region and socioeconomic status. Relative risks (RRs) and population attributable fractions (PAFs) were estimated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 36 publications
(53 reference statements)
1
24
1
1
Order By: Relevance
“…Indeed only three studies (Stalsberg et al, 1989;Wohlfahrt et al, 1999;Li et al, 2008) have reported significant differences according to histological type for at least one aspect of reproductive history; two (Stalsberg et al, 1989;Wohlfahrt et al, 1999) found that increasing age at first birth was associated with a significantly greater relative risk of lobular cancer and/or tubular cancer than of ductal cancer, and one (Li et al, 2008) found a significantly greater effect of age at menarche on lobular compared with ductal breast cancer among postmenopausal women. A large record-linkage study in Sweden (Granstrom et al, 2008) also showed a greater effect of increasing age at first birth for lobular compared with other types, and a smaller effect of low parity on lobular compared with ductal and tubular subtypes; however, there was limited information on potential confounders and no formal tests of heterogeneity by histological subtype were given.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed only three studies (Stalsberg et al, 1989;Wohlfahrt et al, 1999;Li et al, 2008) have reported significant differences according to histological type for at least one aspect of reproductive history; two (Stalsberg et al, 1989;Wohlfahrt et al, 1999) found that increasing age at first birth was associated with a significantly greater relative risk of lobular cancer and/or tubular cancer than of ductal cancer, and one (Li et al, 2008) found a significantly greater effect of age at menarche on lobular compared with ductal breast cancer among postmenopausal women. A large record-linkage study in Sweden (Granstrom et al, 2008) also showed a greater effect of increasing age at first birth for lobular compared with other types, and a smaller effect of low parity on lobular compared with ductal and tubular subtypes; however, there was limited information on potential confounders and no formal tests of heterogeneity by histological subtype were given.…”
Section: Discussionmentioning
confidence: 99%
“…The overall relative risk in women whose age at menarche was 14 or more, compared to less than 12, was 0.95 (0.92 -0.99) for ductal cancer and 0.77 (0.71 -0.83) for lobular cancer. All eight previous studies (Ewertz and Duffy, 1988;Wohlfahrt et al, 1999;Li et al, 2003Li et al, , 2006Li et al, , 2007Garcia-Closas et al, 2006;Rosenberg et al, 2006;Granstrom et al, 2008) included in the meta-analysis of the effect of age at first birth showed a greater effect on lobular than ductal cancer; however, most of these studies had limited power and only one (Wohlfahrt et al, 1999) reported a significant difference in the RRs for lobular and ductal cancers according to age at first birth. Overall, the RR in women whose age at first birth was 30 or more, as opposed to less than 20, was 1.24 (1.20 -1.29) for ductal cancer and 1.66 (1.53 -1.80) for lobular cancer.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Later age of first childbearing and low total parity are commonly associated with higher levels of education and higher SES, due to postponement of childbearing until after the completion of education and the consequent increase of maternal age. There has been a uniform shift towards later first childbearing in most European countries [28][29][30].…”
Section: Increasing Riskmentioning
confidence: 99%